Monitoring chalcogenide ions–guided in situ transform active sites of tailored bismuth electrocatalysts for CO 2 reduction to formate - Zheng Chen; Yi Xiao; Xianji Qiao; Honghui Ou; Chi-Feng Lee; Hsiao-Tsu Wang; Yu-Cheng Shao; Lili Han (Proceedings of the National Academy of Sciences, 2025)
Although bismuth catalysts enable accelerated electrochemical CO 2 -to-formate conversion, the intrinsic active sites and forming mechanisms under operating conditions remain elusive. Herein, we prepared Bi 2 O 2 NCN, Bi 2 O 3 , and Bi 2 O 2 S as precatalysts. Among them, Bi 2 O 2 NCN-derived catalyst possesses optimum performance of electrochemical CO 2 -to-formate, exhibiting an upsurge of Faradaic efficiency to 98.3% at –0.6 V vs. reversible hydrogen electrodes. In-situ infrared and electrochemical impedance spectra trace and interpret the superior performance. Multimodal structural analyses utilizing quasi-in-situ X-ray diffraction, in-situ X-ray absorption near edge structure and in-situ Raman spectra provide powerful support to monitoring the catalysts’ in-situ transforms to metallic Bi, identifying the formation of the active sites influenced by the chalcogenide ions-guided: Carbodiimide promotes to form of the dominant Bi(003) facet exposure, which distinguishes from sulfide- and oxide-preferred dominant Bi(012) facets exposure. Concurrently, theoretical insights garnered from multiscale/multilevel computational analyses harmoniously corroborate the experimental findings. These findings show the pivotal role of chalcogenide in tailoring bismuth electrocatalysts for selective CO 2 reduction to formate, illuminating the significance of controlling structural chemistry in designing catalysts toward high-efficiency renewable energy conversion.